No Evidence for Temperature-Dependence of the COVID-19 Epidemic - Jamil, Tahira; Alam, Intikhab; Gojobori, Takashi; Duarte, Carlos M. (Frontiers in Public Health, 2020)
The pandemic of the COVID-19 extended from China across the north-temperate zone, and more recently to the tropics and southern hemisphere. The hypothesis that COVID-19 spread is temperature-dependent was tested based on data derived from nations across the world and provinces in China. No evidence of a pattern between spread rates and ambient temperature was found, suggesting that the SARS-CoV-2 is unlikely to behave as a seasonal respiratory virus.